The role of international organisations and non-governmental organisations in information support for agricultural policy formulation in Ghana - Villars, J. (Technical Centre for Agricultural and Rural Cooperation, 1999)
This paper describes the main agricultural policy-making bodies in Ghana, the use they make of information and the sources of this information